Dysregulation of RNA Binding Protein Aggregation in Neurodegenerative Disorders - Maziuk, Brandon; Ballance, Heather I.; Wolozin, Benjamin (Frontiers in Molecular Neuroscience, 2017)
The unique biology of RNA binding proteins is altering our view of the genesis of protein misfolding diseases. These proteins use aggregation of low complexity domains (LCDs) as a means to regulate the localization and utilization of RNA by forming RNA granules, such as stress granules, transport granules and P-bodies. The reliance on reversible aggregation as a mechanism for biological regulation renders this family of proteins highly vulnerable to promoting diseases of protein misfolding. Mutations in RNA binding proteins are associated with many neurodegenerative disorders, such as amyotrophic lateral sclerosis (ALS) and frontotemporal lobar dementia (FTLD). The biology of RNA binding proteins also extends to microtubule associated protein tau. Tau is normally an axonal protein, but in stress it translocates to the somatodendritic arbor where it takes on a new function promoting formation of stress granules. The interaction of tau with stress granules also promotes tau aggregation, accelerating formation of the tau pathology that we associate with diseases such as Alzheimer's disease (AD).